An examination of Zimbabwe’s attainment of millennium development goal 2- achieve universal primary education: the case of Insiza Constituency ward 10 - Dlakama, Bongani (Midlands State University, 2017)
The purpose of this research was to explore the challenges which the education sector has faced in meeting Millennium Development Goal 2 which is attainment of universal primary education for all. The research’s main intent was to reveal the progress which the Government of Zimbabwe has made towards achieving universal primary education and to reveal the success and challenges which have been experienced in Insiza Ward 10 towards achieving universal primary education. A sample of 25 people were selected who composed of teachers, school heads, pupils and district education officers. Questionnaires and interviews were used to collect information from the research participants. The research results were based on the data captured in the questionnaires and through the face to face interviews. The education sector in Insiza constituency has faced numerous challenges in its quest to provide quality education and to attain millennium development goal 2. Chief among these challenges include the low budget allocation towards the education sector, as this compromises the ability of schools to improve the learning environments and the provision of teaching and learning materials. The low budget allocation also affects the levels of teacher morale and motivation to do their work. The economic decline has had its impact on rural households and this has seen parents withdrawing their children from primary school due to financial constraints and hunger and poverty. High teacher to pupil ratios also compromise the quality of education as some children are not given the much needed attention that they deserve in order to fully grasp concepts which they are being taught.